c y Chu-yuan Cheng. - Zheng, Zhuyuan; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2020)
China's efforts to stimulate industrial development and economic growth through the allocation of investments are analyzed. Cheng concludes with an overall assessment of the distinctive features of the allocation pattern. Includes 41 statistical tables.
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Capital investments -- China; Electronic books